2004
DOI: 10.1186/cc2937
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: 193 ANCA = antineutrophil cytoplasmic antibody; CSS = Churg-Strauss syndrome; ICU = intensive care unit; MPA = microscopic polyangiitis; PAN = polyarteritis nodosa; PE = plasma exchange; WG = Wegener's granulomatosis. Available online http://ccforum.com/content/9/2/193 AbstractThe second part of this review addresses the treatment and prognosis of the vasculitides Wegener's granulomatosis, microscopic polyangiitis, Churg-Strauss syndrome and polyarteritis nodosa. Treatment regimens consist of an initial remiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…These treatments should be tailored to disease severity, to the nature and extent of organ dysfunction in each individual patient [4,9-11,15,52,54]. Although no data from controlled, randomized, clinical trials are available, guidelines have been developed [52].…”
Section: Reviewmentioning
confidence: 99%
“…These treatments should be tailored to disease severity, to the nature and extent of organ dysfunction in each individual patient [4,9-11,15,52,54]. Although no data from controlled, randomized, clinical trials are available, guidelines have been developed [52].…”
Section: Reviewmentioning
confidence: 99%
“…With the development of therapeutic strategies that include corticosteroids, immunosuppressants, and (plasma exchange [PLEX]), SVV survival rates have considerably improved, from 30 to 75 % at 5 years [ 3 ]. The leading causes of death are related mainly to a life-threatening disease at the time of diagnosis or long-term complications of immunosuppressive therapies, all of which may require intensive care unit (ICU) admission [ 4 , 5 ]. To date, there are only few studies, all retrospective, in which researchers have reported the outcomes of patients with vasculitis admitted to the ICU.…”
Section: Introductionmentioning
confidence: 99%
“…They reported a lower in-ICU mortality varying from 11% to 33%. However, a higher mortality rate may occur in case of pulmonary determinations reaching more than 50% [ 15 ]. Prognostic systems developed to predict outcomes in critical illness [ 16 , 17 ] were evaluated in such patients as well as the level of vasculitis disease activity.…”
Section: Introductionmentioning
confidence: 99%